Hafnium and vanadium nitride heterostrutures applied to machining devices. Issue 1 (January 2016) - Escobar, C.; Caicedo, H.; Caicedo, J.
Abstract HfN/VN heterostructures deposited via magnetron sputtering have been exhaustively studied in this work. Enhancement of both hardness and elastic modulus up to 37 and 351 GPa, respectively, was observed as bilayer periods in the coatings were decreased. The sample with a bilayer period (Λ ) of 15 nm and bilayer numbern = 80 showed the lowest friction coefficient (∼0.15) and the highest critical load (72 N), corresponding to 2.2 and 1.38 times better than those values for the coating deposited withn = 1, respectively. Taking into account the latest results (friction coefficient and critical load), the tungsten carbide (WC) inserts were used as substrates to improve the mechanical and tribological properties of (HfN/VN)n coatings as a function of increased interface number and to manage higher efficiency of these coatings in different industrial applications, like machining and extrusion. Their physical, mechanical, and tribological characteristics were investigated, including cutting tests with AISI 1020 steel (workpiece) to assess wear as a function of the bilayer number and bilayer period. A comparison of the tribological properties revealed a decrease of flank wear (around 24 %) for WC inserts coated with (HfN/VN)80 (Λ = 15 nm), when compared to uncoated tungsten carbide inserts. These results open the possibility for using (HfN/VN) multilayers as coatings for machining devices with excellent industrial performance.